Examining the Methods of Guaranteeing Product Quality from the Perspective of Imami Fiqh, Iranian Law and European Union Law - Akbar Mahmoodi (تحقیقات مالی اسلامی (پیوسته))
According to the origin of the product quality, there are two types of obligation: mandatory and optional. Mandatory guarantee provisions are mandatory rules and there is no possibility of violating them and agreeing against them. Optional guarantee provisions are supplementary rules and according to the principle of sovereignty of will and the principle of freedom of contract, it is possible to violate them and agree against them. Product quality guarantee is divided into two types: one-way commitment and two-way commitment. In unilateral commitment, the guarantor imposes obligations on himself for the benefit of the consumer, and the consumer has no expectations. This type is realized in two forms, the first condition and the first condition, which does not need to be accepted by the consumer in both forms. All Imami jurists, Iranian jurists and European Union law consider unilateral commitment in the form of iqaa as necessary and binding. However, some Imami jurists did not accept the initial condition as binding; But other jurists of Imamia, all Iranian jurists and European Union laws have considered unilateral commitment as an initial condition mandatory. The bilateral obligation to guarantee the quality of the goods is of two types, depending on where the guarantee is inserted: the guarantee in the contract and the guarantee in the independent contract. In both types, the principle of guaranteeing a contract is separate from the first contract, and there is a similar one called customary guarantee. The two-way obligation to guarantee the quality of goods in terms of the guarantor is of two types: the supplier's guarantee and the third party's guarantee. The bilateral obligation to guarantee the quality of the goods is binding, which is resolved by liquidation or annulment of the contract. Product quality assurance is divided into two types: guaranteeing high performance and guaranteeing quality durability, both of which are rational and expected by many buyers; But there is a possibility to differentiate between the two in the product quality guarantee contract.